When Humour Becomes Painful - Critchley, Simon; Lunn, Felicity; Munder, Heike; Zizek, Slavoj (Zürich : JRP-Ringier Kunstverlag AG Zürich, 2005)
Acconci, Vito ; Bag, Alex ; Bareikis, Aidas ; Beagles & Ramsay ; Beuys, Joseph ; Blume, Anna & Bernhard Johannes ; Bock, John ; Breuning, Olaf ; Chapman, Dinos & Jake ; Fabre, Jan ; Feldmann, Hans-Peter ; Fischli & Weiss ; Guggisberg, Anders ; Harrison, Rachel ; Kippenberger, Martin ; Klauke, Jürgen ; Land, Peter ; Liden, Klara ; Lutz, Andres ; Maciunas, George ; Manzoni, Piero ; Miller, John ; Nauman, Bruce ; Parr, Martin ; Polke, Sigmar ; Schnyder, Jean-Frederic ; Wallinger, Mark ; Webb, Boyd ; Zipp, Thomas
When Humour Becomes Painful , Migros Museum für Gegenwartskunst Zürich, 2005-08-27. 2005-10-30
boek